Unintended consequences of enforcement in a cooperative institution: Experimental evidence from Tanzanian fishers. (1st August 2018) - MacColl, Spencer; Onyango, Paul; Reimer, Matthew N.; Stopnitzky, Yaniv
Abstract: Small-scale fisheries in developing countries employ the majority of the world's fishers and are a critical source of income and nutrition for billions of people, yet they frequently suffer from overfishing. To date, institutional reforms have largely consisted of those that have worked well in developed countries, but are poorly suited to the institutional contexts of most developing countries, which are characterized by weak state capacity and poor enforcement. We study the introduction of an enforcement institution among Tanzanian fishers using a novel artefactual field experiment. Results suggest that enforcement mechanisms can sometimes damage cooperative behavior as players shift from cooperative harvest strategies to more destructive ones, which causes the common-pool resource to be depleted faster. We explore the mechanisms by which this undesirable outcome arises and argue that institutional reform should consider that resource users make jointly determined decisions about gear choice, including illegal ones, and harvest rates. Highlights: We study an imperfectly regulated ban on illegal fishing gear with a novel artefactual experiment among Tanzanian fishers. Results suggest that enforcement can sometimes damage cooperation and cause the common-pool resource to be depleted faster. The evidence suggests that institutional reforms should consider multiple margins along which users can make decisions.